Anticancer and antibacterial activities of solanum aethiopicum L., solanum macrocarpon L. and garcinia kola heckel (2021)
Cancer and infectious diseases are among the top ten leading causes of death in developing countries. The discovery and development of newer agents for combating these global health problems cannot be overemphasized. This study was designed to investigate the activities of extracts of Solanum aethiopicum, Solanum macrocarpon and Garcinia kola on cancer and antibacterial pathogens. The Agar well diffusion method was used to evaluate antibacterial activity of the extracts. In vitro anticancer activity against cervical cancer (HeLa), breast cancer (MCF-7) and epidermoid carcinoma of the larynx (HEp-2) was done by microscopic evaluation of morphology and by determination of 50% cytotoxic concentrations (CC50). The CC50 of ethyl acetate extracts of Solanum aethiopicum and Solanum macrocarpon against MCF-7 were 38.79 μg/mL and 41.30 μg/mL respectively, and were significantly lower (p < 0.05) compared to the CC50 of the other extracts. Dichloromethane extract of Garcinia kola was significantly cytotoxic (p<0.05) on cervical cancer (CC50 = 38.13 μg/mL) compared to DCM extracts from Solanum aethiopicum and Solanum macrocarpon. The minimum concentration of methanol extracts of Solanum aethiopicum, Solanum macrocarpon and Garcinia kola that inhibited the growth of Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Klebsiella pneumoniae was 1.56 mg/mL. Solanum aethiopicum, Solanum macrocarpon and Garcinia kola extracts demonstrated significant (p < 0.05) anticancer and antibacterial activities and as such are promising sources of novel plant-derived anticancer and antibacterial drugs.